Effectiveness and renal safety of dupilumab in the treatment of moderate-to-severe atopic dermatitis patients with chronic kidney disease stages 4–5: a real-world cohort study in China - Gang Hu; Quanhong Zhang; Luoyao Yang; Yanglin Hu; Jinbo Chen (Frontiers in Medicine, 2026)
Background While dupilumab is widely used for atopic dermatitis (AD), its safety and effectiveness in patients with severe renal failure remain insufficiently studied. Objective To evaluate the real-world effectiveness and renal safety of dupilumab in this population. Methods This cohort study included 30 adult moderate-to-severe AD patients with Chronic Kidney Disease (CKD) stages 4–5. Patients were divided into a dupilumab-treated group ( n = 17) and a control group ( n = 13) receiving conventional therapy. Effectiveness was assessed using the Peak Pruritus Numerical Rating Scale and Investigator's Global Assessment. Renal safety was evaluated via eGFR and serum creatinine levels, analyzed using linear mixed-effects models. Results The dupilumab group showed a numerically greater PP-NRS reduction at Day 30 (4.6 vs. 2.7 points) with a trend toward sustained improvement; however, the between-group difference did not reach statistical significance in the mixed-effects model ( P = 0.109). IGA scores showed similar trends. Regarding renal safety, despite poorer baseline renal function in the dupilumab group, the degree of renal function decline was not statistically different from that in the control group. Sensitivity analysis excluding patients on dialysis did not alter this conclusion. Conclusion Dupilumab was associated with a numerical trend toward greater improvement in pruritus compared with conventional therapy, and was not associated with statistically detectable acceleration of renal function decline in AD patients with CKD stages 4–5. These preliminary findings require confirmation in larger prospective studies.